Indoor air quality (iaq): an assessment of coarse and fine particles at selected Taska in Kota Bharu, Kelantan - Rahim, Nur Farzuana Abdul (Universiti Sains Malaysia, 2015)
This study was conducted to assess indoor air quality (IAQ) at selected Taska in Kota Bharu, Kelantan. Children are sensitive to indoor environmental pollution. Moreover, up to 90% of their time spend indoors. The study aimed to identify the trend of concentration of suspended particles (PM) and to compare it with the guidelines, to find the differences of PM2.5 and PMw concentration between selected Taska, to compare PM2.5and PM10 concentration between Taska located at roadside area and residential area and to find the relationship of PM2 5and PM10 concentration with the temperature and relative humidity within Taska. The concentrations of PM were measured at 6 selected Taska in Kota Bharu by using Handled 3016 Particle Counter. The data were collected during weekdays in 5 sessions (Sunday to Thursday) at each Taska for 8 hours continuously. An IAQ checklist was used to strengthen the results obtained from this study. The highest concentration of PM2.5 (89.71 ug/m3) was recorded at Taska B on Thursday, while the highest concentration for PM10 (537.81 ug/m3) recorded in Taska A on Wednesday. Overall, the reading of PM25 and PM10 concentrations were exceeded the limits recommended by the National Ambient Air Quality Standard. The trend of PM concentration was found similar for both sizes of PM at six selected Taska in Kota Bharu. Besides, there were differences between PM concentrations for both sizes and all Taska with p=0.000 through Kruskal Wallis analysis. The temperature and relative humidity recorded higher reading compared to the optimum range suggested by Department of Occupational, Safety and Health (DOSH). By using Spearman Correlation test, there were significant difference between temperature and PM2.5 (p=0.000), between PM10 with both temperature and relative humidity (p= 0.000; p=0.001). The high levels of PM recorded were influenced by activity, movement and number of occupants, and surrounding conditions during data collection. As a conclusion, the improvement by responsible parties must be taken in order to maintain and control the IAQ conditions.